The Role of Women's Participation in Development: Empirical Evidence from Indonesia - Della Gusvi Lorenza (Universitas Muhammadiyah Yogyakarta, 2022)
Improving the quality of human resources cannot be separated from the involvement of women. It is because increasing the capacity of women can encourage productive socio-economic activities as well as their capabilities and abilities in community institutions. This study then aims to determine how much women's involvement in government, employment, and household influences the Human Development Index in Indonesia. This study uses panel data analysis of 34 provinces in Indonesia from 2015 to 2020 with a fixed-effect model. The finding of this study is that there is no relationship between the involvement of women in parliament and the human development index. However, there is a positive and significant relationship between women's involvement as professionals and the human development index. The participation of women in the household has the most vital relationship with the human development index, where every 1% increase in the income contribution of women in the home is associated with an increase in the human development index of 1.64 points. Another finding from this study is that women who act as heads of families are associated with decreased human development index. It shows that women will play a more significant role in development as long as their part is not as the head of the family but as a supporter of the family economy.